1986
DOI: 10.1515/polyeng.1986.6.1-4.237
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Dry Spinning of Polyurethane-Urea Elastomers: Theory and Experiment

Abstract: 238

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…To validate this, a set of spinning trials was carried out with an increased DMF/water bath ratio of 65 : 35 at the bath temperature of 15 C, but the spinning was not feasible. Spinning was also not possible with a bath concentration of 60 : 40 at a lower bath temperature of 13 C. Therefore, it has been concluded that a DMF/water bath ratio of 60 : 40 and a bath temperature of 15 C are the optimum conditions under this experimental setup. To study the influence of higher stretch ratios, fibers were spun with increasing stretch ratios (up to 2.5) with a bath ratio of 60 : 40 at 15 C. A significant improvement in the elastic recovery property (Fig.…”
Section: Experimental Validation Of the Design Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To validate this, a set of spinning trials was carried out with an increased DMF/water bath ratio of 65 : 35 at the bath temperature of 15 C, but the spinning was not feasible. Spinning was also not possible with a bath concentration of 60 : 40 at a lower bath temperature of 13 C. Therefore, it has been concluded that a DMF/water bath ratio of 60 : 40 and a bath temperature of 15 C are the optimum conditions under this experimental setup. To study the influence of higher stretch ratios, fibers were spun with increasing stretch ratios (up to 2.5) with a bath ratio of 60 : 40 at 15 C. A significant improvement in the elastic recovery property (Fig.…”
Section: Experimental Validation Of the Design Resultsmentioning
confidence: 99%
“…Three dryjet lengths (15,20, and 25 mm) and three dope solid contents (27, 29, and 31% w/w) were investigated to study their effects on the fiber properties under optimized bath conditions: a bath ratio of 60 : 40, a bath temperature of 15 C, and a stretch ratio of 1.8-2.5.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations